2018
DOI: 10.1162/coli_a_00335
|View full text |Cite
|
Sign up to set email alerts
|

A Joint Model of Conversational Discourse and Latent Topics on Microblogs

Abstract: Conventional topic models are ineffective for topic extraction from microblog messages, because the data sparseness exhibited in short messages lacking structure and contexts results in poor message-level word co-occurrence patterns. To address this issue, we organize microblog messages as conversation trees based on their reposting and replying relations, and propose an unsupervised model that jointly learns word distributions to represent: 1) different roles of conversational discourse, 2) various latent top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 86 publications
(146 reference statements)
0
4
0
Order By: Relevance
“…Extracting and combing paths is time consuming and labeling is labor intensive, so LeadLDA may not be suitable for large online discussion datasets. Li et al [14] exploits discourse in conversations and joins conversational discourse and latent topics together for topic modeling. This model also organizes microblog posts as a conversation tree structure, but does not consider topic hierarchies and model robustness issue like our proposed model.…”
Section: Leveraging Discussion Tree Structure As Priormentioning
confidence: 99%
“…Extracting and combing paths is time consuming and labeling is labor intensive, so LeadLDA may not be suitable for large online discussion datasets. Li et al [14] exploits discourse in conversations and joins conversational discourse and latent topics together for topic modeling. This model also organizes microblog posts as a conversation tree structure, but does not consider topic hierarchies and model robustness issue like our proposed model.…”
Section: Leveraging Discussion Tree Structure As Priormentioning
confidence: 99%
“…The popular tasks in the styles of either RST (Rhetorical Structure Theory) (Mann and Thompson, 1988;Liu et al, 2019) or PDTB (Penn Discourse Tree Bank) (Prasad et al, 2008;Xu et al, 2018) explore the rhetorical relations of discourse units (e.g., phrases or sentences) that cohesively connect them form a sense of coherence. These studies have demonstrated their helpfulness in diverse stream of NLP applications (Choubey et al, 2020), such as sentiment analysis (Bhatia et al, 2015), text categorization (Ji and Smith, 2017), and microblog sum-marization (Li et al, 2018). Nevertheless, limited work examines a social media image as a discourse unit of the pragmatic structure in multimedia contexts, which is a gap to be filled in this work.…”
Section: Related Workmentioning
confidence: 99%
“…Most of them extend Hidden Markov Model (HMM) to produce distributional clusters of words to reflect latent discourse [8,33]. In discourse learning, features are exploited via modeling of conversation tree structure [25], relative position of sentences [20], topic content [32,52], and so forth.…”
Section: Conversation Process Understandingmentioning
confidence: 99%